Phospholipid-mimicking block, graft, and block-graft copolymers for phase-transition microbubbles as ultrasound contrast agents - Huang, Jianbo; Wang, Hong; Huang, Lei; Zhou, Yuqing (Frontiers in Pharmacology, 2022)
Background: Lipid and polymer microbubbles (MBs) are widely used as ultrasound contrast agents in clinical diagnosis, and possess great potential in ultrasound-mediated therapy due to their drug loading function. However, overcoming the limitations of stability and echo enhancement of MBs are still a considerable challenge. Methods: A series novel block, graft and block-graft copolymers was proposed and prepared in this work, and these copolymers were used as shells to encapsulate perfluoropentane as ultrasound contrast agents. First, block, graft and block-graft copolymers with different topological structures were prepared. Then, these copolymers were prepared into block copolymer phase-transition MBs, graft copolymer phase-transition MBs, and block-graft copolymer phase-transition MBs, respectively. Finally, the dexamethasone was used for drug-loaded phase-transition microbubbles model to explore the potential of theranostic microbubbles. Results: Finally, these three resulting copolymer MBs with average size of 4-5 μm exhibited well enhancement of ultrasound imaging under the influence of different frequencies and mechanical index, and they exhibited a longer contrast-enhanced ultrasound imaging time and higher resistance to mechanical index compared with SonoVue in vitro and in vivo. In vitro drug release results also showed that these copolymer MBs could encapsulate dexamethasone drugs, and the drug release could be enhanced by ultrasonic triggering. These copolymer MBs were therapeutic MBs for targeted triggering drug release. Conclusion: Therefore, the feasibility of block, graft, and block-graft copolymers as ultrasonic contrast agents was verified, and their ultrasonic enhancement performance in vitro and in vivo was compared. The ultrasound contrast agents developed in this work have excellent development potential in comprehensive diagnosis and treatment.